2022
DOI: 10.1038/s41586-022-05060-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial multi-omic map of human myocardial infarction

Abstract: Myocardial infarction is a leading cause of death worldwide 1 . Although advances have been made in acute treatment, an incomplete understanding of remodelling processes has limited the effectiveness of therapies to reduce late-stage mortality 2 . Here we generate an integrative high-resolution map of human cardiac remodelling after myocardial infarction using single-cell gene expression, chromatin accessibility and spatial transcriptomic profiling of multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
339
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 310 publications
(349 citation statements)
references
References 106 publications
10
339
0
Order By: Relevance
“…Spatial transcriptomics data from human heart indicated that fibroblast populations were located within defined perivascular and interstitial spatial niches ( Supplementary Fig. 4B – E ) 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial transcriptomics data from human heart indicated that fibroblast populations were located within defined perivascular and interstitial spatial niches ( Supplementary Fig. 4B – E ) 25 .…”
Section: Resultsmentioning
confidence: 99%
“…The advent of single cell multi-omic technologies has afforded the opportunity for the high-resolution detection of novel cell states from healthy and diseased human tissue including the heart 19, 20, 22, 23, 25, 28 . These human cell atlases have provided new insights into the cellular landscape of HF and identified unexpected cell diversity within the stromal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, spatial multi-omic mapping of human myocardial infarction also reveals that a given cell state changes based on the cells’ neighborhood. For example, gene-regulatory programs driving injury of cardiomyocytes, activated phagocytic macrophages and their relation to myofibroblast differentiation in cardiac tissue remodeling are dependent on specific myocardial tissue zones and disease stages [ 26 ]. Hence, tissue macrophage heterogeneity is a critical determinant of immune responses and likely governs the distinct ability of human or mouse macrophages to shape the infarcted heart.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of these specific subpopulations of fibroblasts will need further investigation considering the preeminent role of cardiac fibrosis in cardiac remodelling of different aetiologies. In another study, spatial transcriptomics identified two temporal stages in myocardial scar formation: an early scar with high hypoxia signalling and low ECM production, and a more mature scar with increased ECM production 168 . Genes including TGFB3 and PDGFRA are abundantly expressed in the mature scar, while SERPINE1 is more expressed in the early scar.…”
Section: Novel Molecular Insights From ‘‐Omic’ Studiesmentioning
confidence: 99%